The role of the Mediterranean Diet in preventing the development and complications of lifestyle diseases - a Review - Alicja Kapciak; Julia Górny; Rafał Kaczorowski; Aleksandra Pelczarska; Michał Janiszewski; Marcin Komorowski; Tomasz Forenc; Jaromir Hunia; Jonasz Jurek (Nicolaus Copernicus University in Toruń, 2024)
Introduction The Mediterranean diet, inspired by traditional dietary habits of the Mediterranean region, exhibits anti-inflammatory and protective effects, reducing the risk of civilization diseases such as obesity, type 2 diabetes, and cardiovascular disorders. This diet is characterized by a high intake of plant-based foods, olive oil, and moderate consumption of fish and dairy products. These components provide unsaturated fatty acids, polyphenols, and antioxidants, which positively impact metabolic health and lower the risk of chronic diseases. In the face of the global obesity epidemic and an increasing number of individuals affected by lifestyle-related diseases, the Mediterranean diet offers a promising tool to support a healthy lifestyle. Aim of study This article aims to review current scientific studies evaluating the potential of the Mediterranean diet in preventing and managing civilization diseases. Particular attention is given to its effects on weight loss, improvements in glycemic markers, reductions in low density lipoproteins (LDL) cholesterol levels, and blood pressure control. The article also explores its benefits for athletes' health, as well as its potential to reduce oxidative stress and inflammatory states. Material and methods  A literature review of the PubMed database was conducted, assessing relevant studies on the Mediterranean diet and its impact on lifestyle diseases.